Velocity 2017, New York, New York : video compilation. (O'Reilly Media, 2017)
"An exploration of the best practices for disaster recovery (e.g., where to store the documentation on recovering the documentation server) by Google SRE Tanya Reilly; detailed instruction on using BPF to diagnose seemingly impossible issues in production environments by Sela Group CTO Sasha Goldshtein; a revelation of why you need sponsors as much as mentors to boost your career by Kickstarter VP Lara Hogan. These are just three of the 80+ inspiring keynotes, tutorials, and technical sessions delivered at Velocity NYC 2017. In this video compilation, you'll have access to them all. The keynotes you'll see include Jessica Frazelle (Microsoft) on the complex role open source projects play inside today's highly competitive companies; Cynthia Savard Saucier (Shopify) on the ethical responsibility of designers and developers to not cause harm to users; and other thought-provoking talks by luminaries such as Neha Narula, MIT's lead researcher in cryptocurrency and blockchains, and BMC's Joe Goldberg. The tutorials you can explore feature intensives on OpenTracing, HTTP/2 development, Vault-based microservices secrets management, a data science crash course on modeling and predicting the behavior of large distributed systems, and a how-to on developing resilient microservices with Kubernetes and Envoy. The technical sessions you'll gain access to include Arshan Dabirsiaghi's (Contrast Security) insider scoop on the Struts 2 exploit and the Equifax data breach; Netflixer Joseph Breuer's story on leveraging Cassandra, event sourcing, data snapshots, and data serialization for the Netflix Download feature; VM Brasseur, winner of the 2016 O'Reilly Open Source Award, sharing the secrets of leading productive and happy teams; and Riverbed's Dina Goldshtein's illumination of Event Tracing for Windows, the most important diagnostic tool Windows developers have for monitoring anything, anytime, anywhere."--Resource description page